Cis/trans isomerization of proline peptide bonds in the backbone of cyclic disulfide‐bridged peptides. Issue 6 (9th September 2018) - Sui, Qiang; Rabenstein, Dallas L.
Abstract: Peptides are of interest as potential therapeutic agents, including cyclic disulfide‐bridged peptides because of their limited conformational flexibility and enhanced stability toward proteolysis. To further constrain the flexibility of the peptide backbone, the disulfide‐bridged rings often contain a proline residue, which also serves to facilitate the formation of reverse‐turn structures. However, the proline residue increases the conformational diversity because the tertiary amide peptide bond to proline can exist as significant populations of both the cis and trans isomers. To identify features that affect the distribution between the cis and trans isomers of proline peptide bonds in disulfide‐bridged peptide rings, we have characterized by 1 H NMR the kinetics and equilibria of the cis/trans isomerization of the proline peptide bonds for the linear dithiol and cyclic disulfide‐bridged forms of three families of proline‐containing peptides: Ac‐Cys‐Pro‐[NH(CH2 ) n CO]‐Cys‐NH2, where n  = 1‐4; Ac‐Cys‐Xaa‐Pro‐Cys‐NH2 and Ac‐Cys‐Pro‐Xaa‐Cys‐NH2, where Xaa is Gly, Ala and Val; and Ac‐Cys‐Pro‐His‐(Ala) n ‐Cys‐NH2, where n  = 0‐5. The peptide Ac‐Cys‐Pro‐(4‐AMBA)‐Cys‐NH2, where 4‐AMBA is 4‐aminomethylbenzoic acid, was also studied to determine the effect of a rigid aromatic ring in the peptide backbone on the conformational properties of the Cys‐Pro peptide bond. Equilibrium constants were determined for cis/trans isomerization from the relative intensities of resonances for the cis and trans isomers, and rate constants for cis‐to‐trans and trans‐to‐cis isomerization were determined by the magnetization transfer NMR method. The cis/trans equilibrium is a dynamic equilibrium, and the equilibrium constants vary widely due to the wide range of kinetic stabilities of the various cis and trans isomers. Abstract :